Dissecting the Epigenetic Changes Induced by Non-Antipsychotic Mood Stabilizers on Schizophrenia and Affective Disorders: A Systematic Review - Gardea-Resendez, Manuel; Kucuker, Mehmet Utku; Blacker, Caren J.; Ho, Ada M.-C.; Croarkin, Paul E.; Frye, Mark A.; Veldic, Marin (Frontiers in Pharmacology, 2020)
Background: Epimutations secondary to gene-environment interactions have a key role in the pathophysiology of major psychiatric disorders. In vivo and in vitro evidence suggest that mood stabilizers can potentially reverse epigenetic deregulations found in patients with schizophrenia or mood disorders through mechanisms that are not yet fully understood. However, their activity on epigenetic processes has made them a research target for therapeutic approaches. Methods: We conducted a comprehensive literature search of PubMed and EMBASE for studies investigating the specific epigenetic changes induced by non-antipsychotic mood stabilizers (valproate, lithium, lamotrigine and carbamazepine) in animal models, human cell lines or patients with schizophrenia, bipolar disorder or major depressive disorder. Each paper was reviewed for the nature of research, the species and tissue examined, sample size, mood stabilizer, targeted gene, epigenetic changes found, and associated psychiatric disorder. Every article was appraised for quality using a modified published process and those who met a quality score of moderate or high were included. Results: A total of 2,429 records were identified; 1,956 records remained after duplicates were removed and were screened via title, abstract and keywords; 129 records were selected for full-text screening and a remaining of 38 articles were included in the qualitative synthesis. Valproate and lithium were found to induce broader epigenetic changes through different mechanisms, mainly DNA demethylation and histones acetylation. There was less literature and hence smaller effects attributable to lamotrigine and carbamazepine could be associated overall with the small number of studies on these agents. Findings were congruent across sample types. Conclusions: An advanced understanding of the specific epigenetic changes induced by classic mood stabilizers in patients with major psychiatric disorders will facilitate personalized interventions. Further related drug discovery should target the induction of selective chromatin remodeling and gene-specific expression effects.